APPLICABILITY OF LINEAR ALGORITHM FOR TRACKING MAGNET POSITION AND ORIENTATION - Hartono, Novita
On medical diagnose for gastrointestinal (GI) disease, doctors use endoscope camera which moves inside the patient’s body. Magnetic sensors array can track the location of the camera by using appropriate algorithm. Proper algorithm is needed to produce a high accuracy and fast information. Linear algorithm is faster and has lower complexity compared to nonlinear algorithm. This book is written to analyze the accuracy and limitation of the linear algorithm. With data from 16 magnetic sensors, we compared the reconstruction of the sensors data and the simulation data. The result conclude that the localization error increases with the distance between magnet and sensors, more sensors get higher tracking accuracy, and magnet intensity barely effect the tracking accuracy. Apart from that, we observed that the linear algorithm has a couple limitation due to matrix singularity. The accuracy of the experiment SNR lies between 4 and 20 decibels. We also found from the simulation that the algorithm work properly in a low noise condition.